2010
DOI: 10.1083/jcb.201005160
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 contributes to telomere maintenance and augments global homologous recombination

Abstract: SIRT1 is a positive regulator of telomere length and attenuates age-associated telomere shortening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
211
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(224 citation statements)
references
References 114 publications
(169 reference statements)
7
211
0
6
Order By: Relevance
“…33,42 Further support for this hypothesis is the observation that the deacetylase Sirt1 is selectively expressed in the inner medulla and papilla, and it also is a positive regulator of telomere length, like telomerase. 43 Our observation that osmotic shock, which activates the collecting duct DNA damage response, increased mTert mRNA and protein provides strong support for this possibility.…”
Section: Basic Research Wwwjasnorgmentioning
confidence: 60%
“…33,42 Further support for this hypothesis is the observation that the deacetylase Sirt1 is selectively expressed in the inner medulla and papilla, and it also is a positive regulator of telomere length, like telomerase. 43 Our observation that osmotic shock, which activates the collecting duct DNA damage response, increased mTert mRNA and protein provides strong support for this possibility.…”
Section: Basic Research Wwwjasnorgmentioning
confidence: 60%
“…5,6 Several studies have demonstrated that SIRT1 prevents the onset of senescence in multiple cell types by interfering with senescence-promoting stress signaling. For instance, SIRT1 inhibits telomere erosion (by interacting with telomere repeats), 86 reduces the production of ROS (by regulating MnSOD through FOXO3), and promotes DNA repair (by activating NBS1 and WRN helicase). 86 -88 In ECs, forced expression of SIRT1 prevents oxidative stress-induced premature senescence, whereas SIRT1 inhibition provokes senescence-like phenotypes.…”
Section: Endothelial Aging Phenotypes Are Regulated By Sirtuins and Fmentioning
confidence: 99%
“…SIRT1 also deacetylates FOXO1, FOXO3a and FOXO4, modulating cell cycle and reactive oxygen species (ROS) generation by increasing p27kip1, MnSOD (manganese superoxide dismutase), and GADD45 (growth arrest and DNA damage inducible protein 45) (Brunet et al, 2004;Daitoku et al, 2004;Kobayashi et al, 2005;van der Horst et al, 2004). Studies in SIRT1-deficient and overexpressing mice identified SIRT1 as a positive regulator of telomere length, and showed that SIRT1 attenuates telomere shortening associated with aging (Palacios et al, 2010).…”
Section: Sirt1mentioning
confidence: 99%